TINGKAT KONVERSI DAN BIAYA PAKAN PEMELIHARAAN ITIK MOJOSARI (FASE LAYER) DENGAN PAKAN CAMPURAN KEONG SAWAH - Berek, Ambrosius; Suroto, Karunia Setyowati; Sumarno, Sumarno (Universitas Tribhuwana Tunggadewi, 2017)
This research can are conducted for 1 month starting in April until the month of May 2015. This study aimed to determine and compare the combination treatment in feed rations Ducks Mojosari with duck egg production. The study used a completely randomized design because what if there was a very noticeable difference then continued by real difference. and each treatment can be repeated three times resulting in 21 experimental unit, The results showed that consumption is highest in treatment A0B2 which is a mixture of feed materials between Conch rice field 25% Rice bran 75% with the average of the highest value in the treatment of A0B2 gr / head / day. At intake and feed conversion with the highest value of 7.07%. Average feed conversion highest in A0B3 treatment (without the use of parched rice paddy conch + 45%), the effect of treatment (conch rice fields and parched rice) to feed conversion. It means giving different treatment would result in an average feed conversion was significantly different. Average feed conversion highest in A0B3 treatment (without the use of parched rice paddy snail + 45%). Average daily production of eggs The highest research results on A0B3. and the lowest in treatment A1B1. Based on the results of analysis of variance has been done, note that there is no effect of parched rice and paddy snails to total egg production. Average egg production research results reach the highest egg production in A0B3, and the lowest in treatment A1B1. Based on the results of analysis of variance has been done, it is known that there is no effect of parched rice and paddy snails to total egg production. Penelitian ini dilaksanakan selama 1 bulan mulai bulan april sampai bulan mei 2015. Penelitian ini bertujuan untuk menentukan kombinasi perlakuan dan membandingkan dalam ransum pakan Itik Mojosari terhadap produksi telur itik. Penelitian menggunakan rancangan acak lengkap (RAL) dan setiap perlakuan dapat diulangi 3 kali sehingga menghasilkan 21 Unit percobaan. Dari hasil penelitian menunjukkan bahwa Konsumsi tertingi terdapat pada perlakuan A0B2 sebesar 57.071,50 gr yaitu campuran bahan pakan antara Keong sawah 25% dan Bekatul 75% dengan nilai tertinggi pada perlakuan A0B2 sebesar 380,48 gr/ekor/hari. Pada konsumsi dan konversi pakan dengan nilai tertinggi 7,07 % konversi pakan tertinggi terdapat pada perlakuan A0B3 (Tanpa penggunaan nasi aking + Keong sawah 45%),pengaruh pemberian perlakuan (keong sawah dan nasi aking) terhadap konversi pakan. Konversi pakan tertinggi terdapat pada perlakuan A0B3 (Tanpa penggunaan nasi aking + keong sawah 45%). Produksi harian telur tertinggi pada A0B3 sebesar 0,72 gr dan terendah pada perlakuan A1B1 sebesar 0,32 gr. Tidak terdapat pengaruh pemberian nasi aking dan keong sawah terhadap total produksi telur. Produksi telur tertinggi pada A0B3 sebesar 20,33 gr dan terendah pada perlakuan A1B1 sebesar 8,67 gr. Tidak terdapat pengaruh pemberian nasi aking dan keong sawah terhadap total produksi telur.